Psychogenic Foreign Accent Syndrome: A New Case - Keulen, Stefanie; Verhoeven, Jo; De Page, Louis; Jonkers, Roel; Bastiaanse, Roelien; Mariën, Peter (Frontiers in Human Neuroscience, 2016)
This paper presents the case of a 33-year-old, right-handed, French-speaking Belgian lady who was involved in a car accident as a pedestrian. Six months after the incident she developed a German/Flemish-like accent. The patient's medical history, the onset of the FAS and the possible psychological causes of the accent change are analyzed. Relevant neuropsychological, neurolinguistic, and psychodiagnostic test results are presented and discussed. The psychodiagnostic interview and testing will receive special attention, because these have been underreported in previous FAS case reports. Furthermore, an accent rating experiment was carried out in order to assess the foreign quality of the patient's speech. Pre- and post-morbid spontaneous speech samples were analyzed phonetically to identify the pronunciation characteristics associated with this type of FAS. Several findings were considered essential in the diagnosis of psychogenic FAS: the psychological assessments as well as the clinical interview confirmed the presence of psychological problems, while neurological damage was excluded by means of repeated neuroimaging and neurological examinations. The type and nature of the speech symptoms and the accent fluctuations associated with the patient's psychological state cannot be explained by a neurological disorder. Moreover, the indifference of the patient toward her condition may also suggest a psychogenic etiology, as the opposite is usually observed in neurogenic FAS patients.